Efektivitas Pembiayaan Mudharabah Dalam Meningkatkan Kinerja UMKM (Studi Kasus pada BMT NURUL JANNAH GRESIK) - Musdiana, Rohmah Niah; Herianingrum, Sri (Jurnal Ekonomi dan Bisnis Islam, 2015)
Financing is one of the products of Islamic banking, but because of the many requirements that must be complited by SME who need it then their capital needs are not fulfilled. One of the financial institutions that have the same product is Baitul Maal wat Tamwil (BMT).BMT present to fulfill the capital needs of the SMEs who have the problem of capital. By this existing phenomena, this study intends to look at the effectiveness of the financing in order to improve the performance of this SMEs. This research aims to determine whether the financing is provided by BMT Nurul Jannah Gresik effective in improving the performance of SMEs that become their customers and see what business improvement has been achieved such as increased turnover, business assets, revenues, and stability efforts. The results of this research to get the findings that the financing is provided by BMT Nurul Jannah Gresik very effective in improving the performance of SMEs who have become clients in addition to the financing is given BMT Nurul Jannah assist SMEs in meeting the other without prejudice to individual principles of trust and trust that they receive.Keyword :Â Effectiveness, mudharaba, Baitul Maal wat Tamwil, SMEs